#TITLE_ALTERNATIVE# - SINA (NIM 12204065); Pembimbing: Ir. Leksono Mucharam, M.Sc., Ph.D., IBNU
This paper discuss about the effect of surfactant injection on the oil recovery factor in a 15 cm x 15 cm x 2.5 cm 3D reservoir physical model, made of mixing both sand and cement on a specified composition and used as artificial oil reservoir. The approaching method of this 3D model is more reliable and acceptable as a reservoir representative than one dimension displacement in core plug. In order to recover oil from 3D reservoir physical model, amount of produce water injected to simulate both primary and secondary oil recovery in laboratory. The recovery factor for this waterflood method was about 28.28 %. Meanwhile the residual oil which left in reservoir model would be then recovered by surfactant injection both using conventional and soaking method. The total recovery factor due to surfactant injection by conventional EOR method increased up to 31%, while for the three phases of soaking method was about 37.81 %, 44.66 % and 51.65 %.